Thinking Process of Junior High School Students in Solving Mathematics Problems Based on Emotional Quotient - Rafika Kamila Sari; Endah Budi Rahaju (MATHEdunesa, 2023)
Thinking process is a series of cognitive processes that occur in someone’s mental and mind including the stages of remembering, considering, making arguments, and making decisions. Differences in students' thinking processes in solving math problems can be influenced by emotional quotient. This study uses three stages of the thinking process which include (1) Forming understanding, (2) Forming opinions, and (3) Forming conclusions. The aim of this study is to describe the thinking processes of junior high school students with high and low emotional quotient in solving problems of flat side of space. This study is a qualitative descriptive study. The instruments used were the Emotional Quotient Questionnaire, Mathematical Ability Test, Problem Solving Test, and interview guides. This study was conducted on class VIII students of junior high school with the subject of one high emotional quotient student and one low emotional quotient student. The results of this study indicate that in the stage of understanding the problem, both students with high and low emotional quotient can re-explain the contents of the given problem, determine what is known and what is asked in the problem, and choose information to use and information that is not used to solve the problem. In the stage of making a problem solving plan, both students with high and low emotional quotient can determine concepts related to the problem. Students with high emotional quotient can determine more than one way of solving and choosing the method used to solve problems, while students with low quotient only know one way of solving problems. In the stage of carrying out the plan, high emotional quotient students can implement the steps according to the previously made settlement plan to obtain the final answer, while low quotient students cannot implement the steps to the end because she is unsure of the steps chosen. In the stage of re-examining the answers, students with high emotional quotient can determine the final conclusion of the results, while students with low emotional quotient cannot determine the final conclusion because she cannot solve the problem.